Enhancing Dexterity And Speed Of Movement Through Yogic Practices And Neuromotor Training In Female Students - Mr. A.THOOYA ALEX; Dr.C.DURAI (Educational Administration: Theory and Practice, 2024)
A proactive mindset among young women fosters resilience and adaptability, equipping them to navigate diverse life challenges with grace and vigor while simultaneously nurturing physical literacy. Within this framework, finger dexterity and motor speed emerge as essential components of fine motor control, reflecting the efficiency of neuromuscular coordination and the ability to execute rapid, precise movements (Telles, Raghuraj, Arankalle, & Naveen, 2014, p. 22). This study aimed to evaluate the effects of yogic practices and neuromotor training on two critical motor skills dexterity and speed of movement among female undergraduate education students. Forty-eight female students, aged from 22 to 26, enrolled in a college of education (B.Ed), were randomly assigned to one of three groups: the Yogic Practice Group (YPG), the Neuromotor Training Group (NMTG), and the Control Group (CG). While the CG did not participate in any structured intervention, the YPG and NMTG completed six-week training programs. Dexterity was assessed using the Finger Dexterity Task, and speed of movement was measured via the 30-meter sprint test. Pre-test scores were used as covariates in the ANCOVA analysis. The results revealed significant improvements in both dependent variables following the intervention. Dexterity showed greater enhancement in the YPG, whereas speed of movement was notably higher in the NMTG compared to the CG. These findings suggest that yogic practices are more effective in improving dexterity, while neuromotor training yields superior outcomes in enhancing speed of movement among female undergraduate education students.